Chemoselective synthesis of 5, 4′-imidazolinyl spirobarbiturates via NBS-promoted cyclization of unsaturated barbiturates and amidines. Issue 22 (18th May 2021) - Xu, Hui; Huang, Rong-Lu; Shu, Zhu; Hong, Ran; Zhang, Ze
Abstract : The cyclization of unsaturated barbiturates and amidines promoted by  N -bromosuccinimide furnished a variety of structurally novel 5, 4′-imidazolinyl spirobarbiturates with high chemoselectivity, good yields and remarkable functional group tolerance. Abstract : A selective cyclization of unsaturated barbiturates and amidines promoted by N -bromosuccinimide has been successfully developed to afford a vast variety of 5, 4′-imidazolinyl spirobarbiturates in moderate to good yields. The present protocol features broad substrate scope, facile work-up procedure and mild reaction conditions, providing a novel strategy for the highly selective and efficient construction of structurally diverse spiroimidazolines.